Penguatan Keterampilan Guru dalam Pemanfaatan GeoGebra sebagai Media Pembelajaran Program Linear - Christina Kartika Sari; Nida Sri Utami; Adi Nurcahyo; Mohamad Waluyo; Sri Rejeki; Wulan Galuh Rahma Perwita (Prima Abdika : Jurnal Pengabdian Masyarakat, 2022)
To support students facing rapid technological development, teachers must provide real experience in the learning process. Linear programming materials that require visualization in their understanding can be taught by integrating GeoGebra software. This community service aims to strengthen teacher skills in using GeoGebra for linear programming learning media. Community service is carried out through training and mentoring with an active learning participant approach. The activities are carried out through three core stages: teacher training in mastering the GeoGebra interface, assistance in visualizing linear programming problems, and aid in solving linear programs. Although most of the participants stated that GeoGebra could help learn linear programming in the classroom, its implementation needs to consider various aspects, such as the preparation of learning tools and equipment, learning time, and student readiness.